Arsip sebagai Simpul Pemersatu Bangsa: Array - Djoko Utomo (Jurnal Kearsipan, 2010)
This paper tried to see archives in the context of life of a society, country, and nation. Based on the discussion, it can be concluded that archives play important roles in societies, countries, and nations. In fact, archives bind and tie the unity of the nation. It is a reality that cannot be denied. Truly, it is apposite with ANRI vision “functioning archives to bond the unity of the nation”. The purpose of this paper is to grow and bring up the passion toward our motherland, to raise unity among youngsters, and to put up the excitement that we are all brothers and sisters in one nation which nowadays that kind of feeling is getting lessen owingto the influence of the globalization.